FAKTOR YANG MEMPENGARUHI PEMILIHAN KARIR AUDITOR PADA MAHASISWA STIE SURAKARTA - Anggraini, Caecilia Dian; Kholis, Nur (Jurnal Riset Keuangan dan Akuntansi, 2023)
The purpose of this study is to identify the variables that influence the decision of STIE Surakarta students to work as auditors. The main data was collected through a survey distributed to accounting students in semester 7 of STIE Surakarta. A sample of 44 respondents was obtained by accidental sampling. The data were analyzed by multiple linear regression. The research findings show that professional training, professional recognition, and labor market considerations have a positive and significant effect on the career choice of auditors of STIE Surakarta students. However, the gender variable has no significant effect and has a negative effect on the auditor's career choice. Overall, professional training, professional recognition, labor market considerations, and gender all affect auditor career choice. Keywords: Professional Training, Professional Recognition, Labor Market Considerations, Gender, Career Selection.